Patterns and Management of Zygomaticomaxillary Complex Fractures in Motorbike Accidents - Sardar, Tariq; Farooq, Syed Umer; Sheikh, Gulrukh (ADVANCES IN BASIC MEDICAL SCIENCES, 2019)
Aim: Zygomatic bone fractures occur commonly due to its prominent position. Road traffic accidents are leading cause of these fractures in the developing countries. The study aims to determine the common patterns of zygomatic complex fractures in motorbike accidents and the different treatment options used for their management. Material and methods: This study was done in the department of Oral and Maxillofacial surgery, Khyber College of Dentistry, Peshawar, from Jan 2015 to March 2017. Total of 240 patients who suffered zygomatic bone fractures from motorbike accidents were analyzed. Patterns were classified into six types based on Knight and North classification. Results: The mean age of the patients included in this study was 25.8±10.3 years.The most common pattern was Type IV (40.4%) followed by Type V (27.9%) while least common pattern was Type I (2.1%). All the type I fractures were managed conservatively while type II were treated with reduction only. Most of type III fractures were treated by 1 point fixation, type IV and V mostly by 2 point and type VI with 3 point fixation. Conclusions: Men in their 3rd decade of life commonly suffer from zygomatic bone fractures due to motorbike accident. The most common patterns in these fractures are medially rotated (type IV) and laterally rotated body fractures (type V) that required at least 2 point fixation for their optimum management. Key words: pattern, treatment, zygomaticomaxillary fractures, motorbike accidents